Case Survey for Assessing Community-Based Enterprise: A Research Design - Soviana Soviana (Justus-Liebig-Universität, 2013)
Despite the increasing implementation of community-based enterprise (CBE), two problems are prevailing: (1) lack of comprehensive understanding about the organization of CBE and (2) lack of generalizability of the individual findings. In response to these problems, this paper aligns its research on organizational theory and it aims to present a research design, introducing and explaining the possibility of implementing the case survey methodology for assessing CBE.
Keywords: 330; community-based enterprise; organizational architecture; performance; case survey